Pelatihan Perintisan dan Manajemen Lembaga Bimbingan Belajar bagi Mahasiswa Undikma Sebagai Upaya Meningkatkan Jiwa Social Entrepreneurship - Tri Setianingsih; Siti Syafiyatul Qomariyah; Bq. Zuhrotun Nafisah; Sri Ariani; Muhammad Arief Rizka (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This service activity aims to provide knowledge and ability to pioneer and manage a tutoring institution for Undikma students as an effort to improve the spirit of social entrepreneurship. The method of implementing this community service activity is by diffusion-based training of knowledge. This activity was held at the Faculty of Culture, Business and Management Undikma and was attended by 20 students as training participants. The implementation of this service activity has been well organized, it is proven that some of the students who have participated in the training have succeeded in making their own tutoring services as much as 25%, while 25% of participants are still freelance employees and 50% are still trying to make tutoring.